Perbedaan Derajat Keparahan Akne Vulgaris berdasarkan Pemakaian Alphadan Beta Hydroxy Acid - LAKSMITA SEKAR ANGGRAENI; RIETTA KUMALA, ASAMI; NGESTI RAHAYU, IINDRI (Hang Tuah Medical Journal, 2023)
Background : Indonesia has a tropical climate that gets very strong sun exposure. With extreme weather conditions, various skin problems can be seen, one of which is acne vulgaris. Topical therapy is the preferred choice for the treatment of mild to moderate acne and is also helpful for the treatment of severe acne, such as alpha hydroxy acids and beta hydroxy acids (AHAs and BHAs). Objective : To determine the differences in the severity of acne vulgaris based on the use of alpha hydroxy acid and beta hydroxy acid (AHA and BHA) in 6th semester students of the Hang Tuah University Faculty of Medicine. Methods: An analytic observational method in a cross sectional study with a simple random sampling method. The study was conducted from April to December using 58 samples by distributing questionnaires through the google form link. Results : The Mann-Whitney U statistical test between users and non-users of alpha hydroxy acid and beta hydroxy acid (AHA and BHA) showed a significance 0,068. So there was no difference in the two groups. Conclusion : The most classification of acne vulgaris severity is mild in female students who use and do not use alpha hydroxy acid and beta hydroxy acid (AHA and BHA). Keywords : AHA and BHA, Acne Vulgaris, Facial Skin.